O Senso de Pertencimento e a Autoeficácia em estudantes do ensino técnico integrado dos cursos de informática - Fernandes, Ákila Luz (2024)
The Sense of Belonging is the latent construct defined as the understanding of how and to what extent an individual feels belonging or not to a specific context and/or environment. Self-efficacy, on the other hand, is the perception that an individual has of themselves regarding their capacity (or lack thereof) to perform a task. Recent studies show that both constructs are relevant to the persistence and success of students in computer science courses. However, there is a gap in research exploring these constructs in an integrated manner in vocational education compared to studies focused on higher education. Vocational education institutions are important in Brazil since they are one of the main contexts for programming education at secondary level. Moreover, in many institutions of vocational education, programming is mandatory, and there is gender parity. The goal of this research is to fill this research gap by longitudinally investigating the Sense of Belonging and Self-efficacy in vocational schools in Brazil and the potential gender differences between these constructs. After conducting a pilot for the adaptation of selected instruments in the literature, the questionnaires were administered at three different moments during the academic semester to students from the Federal Institute of Bahia (IFBA) and Mato Grosso do Sul (IFMS). The results show similar levels of Sense of Belonging and Self-efficacy between men and women, but the correlation between the constructs, in general, is weak, with just some elements with medium correlation.